Mapping height variations of seasonal ice cover at the Martian South Pole - Xiao, Haifeng; Stark, Alexander; Steinbrügge, Gregor; Thor, Robin; Schmidt, Frédéric; Oberst, Jürgen (2021)
Previously, we have proposed and validated the co-registration of local dynamic Mars Orbiter Laser Altimeter (MOLA) profile segments to static Digital Terrain Models (DTMs) as an approach for obtaining seasonal CO2 ice cover height variations on Mars. Building upon this, we introduce a post-correction procedure called “bi-RPCA” to further lower residual errors in the profiles and improve the precision of the height variation measurements. The ultimate goal is to apply this method to MOLA, SHAllow RADar (SHARAD) radar altimetry to generate long-term seasonal height change time series at the Martian poles with high spatial and temporal resolution.